Improved molecular diagnosis of facioscapulohumeral muscular dystrophy (FSHD): validation of the differential double digestion for FSHD. Issue 6 (June 1997) - Upadhyaya, M; Maynard, J; Rogers, M T; Lunt, P W; Jardine, P; Ravine, D; Harper, P S
Abstract : A major advance in the molecular diagnosis of facioscapulohumeral muscular dystrophy is the recently reported elimination of confounding DNA fragments arising from homologous sequences located at 10q26. In order to evaluate the specificity and sensitivity of this important diagnostic test, we have compared a group of 130 patients fulfilling the diagnostic criteria for FSHD with 200 control subjects not known to have an increased risk of having an FSHD mutation. Among the FSHD cases the smallest BlnI/EcoRI fragment sizes ranged from 10 to > 48 kb with 94.6% (95% CI 89.2-97.8%) of cases having fragment sizes of 34 kb or less. Among the 400 chromosomes from controls the smallest BlnI/EcoRI fragment observed with the EcoRI/BlnI double restriction enzyme digest was 38 kb +/- 2 kb, suggesting a test specificity at a fragment size < 34 kb of or very near to 100% (lower 95% CI 98.2%). Test sensitivity at < 34 kb is estimated at 94.6% (95% CI 89.2-97.8%), all outliers having fragments > 38 kb. The Southern blot analysis with DNA probe p13E-11 has created a valuable molecular diagnostic test for FSHD.